2017
DOI: 10.4172/2167-0250.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Alternations in miRNA Expression in Chronic Stress-Induced Ageing of Leydig Cells

Abstract: Purpose: Chronic stress represents a critical influence on ageing of Leydig cells in testis. We aimed to investigate expression changes of microRNA (miRNA) associated with stress-induced ageing in Leydig cells. Methods:Brown Norway rats were separated into three groups, young control group, stress group and age group. Physiological changes, including serum corticosterone and testosterone levels, 11β-HSD (11β-hydroxysteroiddehydrogenase) activity, GSH/GSSG (glutathione/glutathione disulfide) ratio and DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Since this result also showed the significant reduction of testosterone in modified CUMS, it is explained that why the androgen‐dependent organs such as testis and epididymis have low absolute weights as compared to the control. Moreover, CUMS could reduce antioxidant enzymes and damage DNA structure in Leydig cells (Zhou et al., 2017). This study showed the decrease of body weight and testicular weights similar to that in the CUMS animals as previously demonstrated (Sakr et al., 2015; Salami et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since this result also showed the significant reduction of testosterone in modified CUMS, it is explained that why the androgen‐dependent organs such as testis and epididymis have low absolute weights as compared to the control. Moreover, CUMS could reduce antioxidant enzymes and damage DNA structure in Leydig cells (Zhou et al., 2017). This study showed the decrease of body weight and testicular weights similar to that in the CUMS animals as previously demonstrated (Sakr et al., 2015; Salami et al., 2020).…”
Section: Discussionmentioning
confidence: 99%